60 pī chīwit nakwichākān sū ngān bānmư̄ang, Sō̜. Nō̜phō̜. Suchai Čharœ̄nrattanakun - Suchai Čharœ̄nrattanakun, 1955-; Phadutchai Khīanthō̜ng (Hēn Wœ̄k, 2015)
Life and achievements of Professor Suchai Charoenrattanakun, a former Minister of Ministry of Public Health, and Acting Minister of Ministry of Information and Communication Technology, Thailand; volume commemorating his 60th birth anniversary in 2015.